Phase delay of short-period tsunamis in the density-stratified compressible ocean over the elastic Earth. Issue 3 (17th May 2021) - Sandanbata, Osamu; Watada, Shingo; Ho, Tung-Cheng; Satake, Kenji
SUMMARY: Tsunamis are often modelled as surface gravity waves of incompressible homogenous water propagating over a rigid seafloor. Previous studies have noted that when computing long-period tsunamis travelling at trans-oceanic distances with dominant periods of thousands of seconds, we need to consider four factors that are not included in the surface gravity wave theory: compressibility of seawater, density stratification of oceans, elasticity of the Earth and gravitational potential change associated with the tsunami motion. However, their effects on short-period tsunamis with dominant periods below 1000 s have not been examined. Here, we investigate how the four factors influence short-period tsunamis. Theoretical analyses and 1-D simulations using phase speeds of different tsunami models indicate that the resultant phase delay of short-period tsunamis becomes apparent after ∼1000 km propagation, mainly because of the first three factors. We then introduce a new phase correction method for dispersive short-period tsunamis with consideration of period-dependent ray paths and apply it to a 2-D simulation of a short-period tsunami from a submarine volcanic earthquake near Japan in 2015. The correction of the traveltime of a synthetic waveform by including the four factors amounts to ∼40 s at a distant station 1430 km away from the source, whereas the effects of the four factors on the waveforms are negligibly small at stations < ∼500km from the source. The observed traveltime at the ocean bottom pressure (OBP) gauge with a sampling interval at 15 s of the distant station can be explained only when these factors are incorporated into synthetic waveforms, indicating the effects due to the four factors are detectable by high-sampling OBP gauges that are deployed over broad oceanic regions.